Peran pustakawan dalam menanggulangi bibliocrime terhadap koleksi anak (Pendekatan edukatif dan preventif): Pustakawan; Bibliocrime; Edukatif dan Preventif - Ariska Idamayanti (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Bibliocrime is a serious crime against library materials and is increasingly widespread in libraries because it can threaten the sustainability of library materials, both caused by children and adult users, especially bibliocrime that occurs at the East Tanjung Jabung Regency Library and Archives Office in the children's collection room. This study aims to examine the role of librarians in tackling bibliocrime in children's collections through educative and preventive approaches at the East Tanjung Jabung Regency Library and Archives Office. This study uses qualitative methods with data collection techniques in the form of interviews and observations. The results of this study indicate that some of the bibliocrime actions that occurred at the East Tanjung Jabung Regency Library and Archives Office were theft, mutilation, unauthorized borrowing and vandalism. However, the most common acts of bibliocrime are tearing and vandalism. Then, to overcome the problems regarding bibliocrime, librarians apply two approaches, namely the educative approach carried out through user education and giving directions and warnings to users. As for the preventive approach provided by librarians through increased supervision and security, checking systems for borrowing and returning and providing lockers. With this educative and preventive approach, it is hoped that the act of bibliocrime will be reduced and users will have an awareness of the importance of protecting library material collections.